An A-π-D-π-A-Type Organic Semiconductor Based Optoelectrical Device With Photo Response and Optical Memory Behaviors - Feng, Shiyu; Dai, Donghuan; Lin, Yao; Chen, Shuo; Wu, Xiaosong; Huang, Weiguo (Frontiers in Materials, 2020)
A novel photoactive semiconductor (named as IDTOT-4F) with an A-π-D-π-A-type configuration is synthesized. It contains an electron-donating fused ring (D) as the core flanked with two π-spacers and is end-capped with two electron-withdrawing units (A). The intramolecular charge transfer effect endows IDTOT-4F with strong and broad light absorption and a relatively narrow band gap (1.46 eV). Thin-film optoelectrical devices based on IDTOT-4F exhibit both n-type and p-type switching behaviors. Besides, the p-channel device shows significantly photoresponsive performance with the maximum P (photo/dark current ratio), R (photoresponsivity), and D* (detectivity) values of around 60, 0.07 A W−1, and 2.5 × 1010 Jones, respectively. Further, IDTOT-4F based optoelectrical devices exhibit good optical memory characteristics with a time constant τ1 of 4.6 h, indicating its applicability to nonvolatile optical memory devices. The results provide new insights into the photoresponsive behavior of fused-ring semiconductors and pave the way for the design of nonvolatile optical memory devices.